London 2013, 75th Eage Conference en Exhibition Incorporating SPE Europec 2013
DOI: 10.3997/2214-4609.20130931
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rock Surface Charge in the Carbonated Water Flooding Process

Abstract: SUMMARYCarbonated Water Flooding (CWF) is an alternative EOR method where an oil reservoir is flooded with carbonated (CO2-enriched) water. It is a promising solution for improving oil recovery that benefits from oil viscosity reduction, an increase in oil relative permeability and enhancement of oil mobility. At the same time CWF is a possible mitigation option for the increasing carbon dioxide concentration in the atmosphere and a chance for safe disposal of CO2 underground. We present Bentheimer sandstone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…However, several studies have reported the wettability alteration of quartz surfaces from strongly to less water-wet in contact with supercritical CO 2 . ,,,, This inconsistency originates from differences in the surface charges of quartz and Bentheimer sandstone. Although Bentheimer sandstone is mainly composed of quartz, even a low content of clay (i.e., 2.5% Kaolinite and so on) plays an important role in the surface charge of particles …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, several studies have reported the wettability alteration of quartz surfaces from strongly to less water-wet in contact with supercritical CO 2 . ,,,, This inconsistency originates from differences in the surface charges of quartz and Bentheimer sandstone. Although Bentheimer sandstone is mainly composed of quartz, even a low content of clay (i.e., 2.5% Kaolinite and so on) plays an important role in the surface charge of particles …”
Section: Resultsmentioning
confidence: 99%
“…Although Bentheimer sandstone is mainly composed of quartz, even a low content of clay (i.e., 2.5% Kaolinite and so on) plays an important role in the surface charge of particles. 56 For the quartz surface, an increase in contact angle with pressure has been attributed to the decreased charge of the silica surface under the acidic pH of the CO 2 -equilibrated aqueous phase. 12,55,57 The pH of the aqueous phase influences the surface charge of the particles.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of components and properties of the coal surface on wettability mainly reflected in organic macromolecules, elemental content, and inorganic minerals. 22 Murata 23 measured the CAs of coal pellets in the atmosphere and reported that CAs depend on the oxygen and hydrogen content of these surfaces. Li et al 24 reported that wettability mainly depends on hydrophilic and hydrophobic groups of coal surfaces.…”
Section: Introductionmentioning
confidence: 99%